Rabi’ah al-Adawiyah : Pemikiran dan akhlak dalam bertasawuf - Nisa, Alifia Khoirun (Maliki Interdisciplinary Journal, 2024)
There is a female Sufi figure in the city of Basrah who was born in a family of deprivation and in a family with a zuhud life. She is very famous for her closeness to Allah SWT with the concept of love for God in the world of Sufism, namely Rabi’ah al-Adawiyah. Rabi’ah’s teaching of Sufism, known as mahabbah ilahiyah, is one of the teachings of Sufism that can bring peace and tranquility. Many values are contained in the teachings of Rabi’ah Sufism, such as fostering an attitude of harmony in religious life, nation, and state so as to create peace in society. The concept of mahabbah is divided into 3 levels, namely the mahabbah of ordinary people, the mahabbah of shiddiq people, and the mahabbah of wise people. In Rabi’ah al-Adawiyah’s thought, good akhlaq includes repentance, ridho, love, the essence of faith, and humility from riya’. And many Sufis were inspired by the thought and life of Rabi’ah al-Adawiyah.